The Effects Of School Privatisation On Various Socioeconomic Groups: A Research Study - Zhu Yulan; Khatipah binti Abdul Ghani; Rozaini Binti Rosli (Revista Electronica de Veterinaria, 2024)
To meet the ever-increasing demand for education throughout the nation, the education sector has become more privatised. The provision of education is being transferred from the state to private providers in order to better achieve the policy objectives of expanding access to and participation in basic education, (ii) enhancing learning results and overall efficiency, and (iii) cultivating more fairness in educational opportunities. The manner in which a nation chooses to educate its young people may have a significant impact on the country's trajectory into the future. In spite of the beneficial benefits that private education has had on the larger community, the sector's surging popularity and rapid development have given rise to a number of new concerns. For purely pragmatic reasons, it is of the utmost importance to investigate the problems that arise from the move towards privatisation.